Network structure and electromechanical properties of viscose-graphene conductive yarn assembles. (April 2017) - Ma, Hui; Wu, Wen; Cao, Jianda; Yue, Binbin; Zhang, Huanxia
Abstract: Conductive yarns were successfully prepared through the assembly and reduction of graphene oxide on the surface of viscose yarns and the relationship between network structure of yarn assembles and electromechanical properties of knitted or weave fabrics was analyzed. The loop and interlacing structure, which were provided by knitted and weave fabrics respectively, could result in different electrical properties under external stress because of the change of volume or contacting resistors of yarn assembles. Herein, the stitch structure of fabrics was simulated as circuit model consisted of volume resistance or contact resistors. Based on such models and volume and contacting resistors of yarns, the simulated results agreed reasonably with the experimental data and major trends of both results were consistent. In addition, with the deformation of topology structure of fabrics under drawing, the fineness of yarns and densities of fabrics became changed, causing the increase or decrease of transfer rate of electrons along the yarns. The results provided a theory basis for the design and preparation of flexible conductive devices with the potential applications of energy storage/conversion, wearable sensor, transparent conducting films, flexible cell and so on. Graphical abstract: